Islamic Philanthropy (Zakat and Waqf) As A Form of Economic Crisis Management - Nur Khayin Muhdlor (Budapest International Research and Critics University, 2022)
The purpose of this study is to describe the practice of Islamic Philanthropy, especially in the field of zakat and waqf. The nect objective is to analyze the correspondence of phenomenon of Islamic philanthropy, especially in the field of zakat and waqf, with the problem of the economic crisis. The method used in this research is descriptive qualitative. The data collection technique used the literature study method, called the study of documentation. Data analysis in this study used qualitative analysis and then draws conclusions using the deduction method.The result of this study indicate that the practice of philanthropy is a form of human’s love expression for others which is implemented by giving, both material and non-material to those in need. Etymologically, philanthropy consists of twi Greek words, philia (love) and anthrophos (human), which in general can be interpreted as a form of love for fellow human beings. There are four dimensions of Islamic philanthropy, called zakat, infaq, sadakah, and waqf, but this study focuses on zakat and waqf. Zakat itself is the expenditure of part of the property according to sharia rules and is distributed collectively to the poor, while waqf is the expenditure of part of the property with the purpose of increasing the productivity of the people. With these two practices, the economic crisis is likely to be overcome to some extent.